The role of job satisfaction as mediated in the effect of work environment on turnover intention - Derris Aliayunika Jawad; Muhamad Ekhsan (Institute of Computer Science (IOCS), 2023)
Turnover Intention in this study is defined as a situation where employees leave the company due to disturbances in the work environment, the dynamics of teamwork, and the performance of the PT NA This study aims to determine the direct effect of the Work Environment on Turnover Intention through job satisfaction as a mediating variable. The object of research at PT NA. This research was conducted using a quantitative method with SEM SmartPLS software as an analytical tool. The number of samples obtained by sampling technique by random sampling using the slovin formula totaled 67 employees. Data collection was carried out via Google from in filling out the questionnaire. The results of this study indicate that the Work Environment has a significant effect on Job Satisfaction, Job Satisfaction has no significant effect on Turnover Intention, Work Environment has no significant effect on Turnover Intention. In addition, it is also known that the variable Job Satisfaction can mediate the relationship between the Work Environment and Turnover Intention. This shows that Job Satisfaction has no impact on Turnover Intention caused by the Work Environment at PT NA. This is because even though there is high job satisfaction in employees it will not eliminate the intention to change workplaces caused by an uncomfortable work environment. Furthermore, to increase employee job satisfaction, PT NA needs to pay attention to the quality of supervision of the employees under it. Employees who are well supervised by their superiors tend to be able to carry out their work well, so that job satisfaction can be achieved.